Neurosarcoidosis: two case reports with multiple cranial nerve involvement and review of the literature - Mijajlovic, Milija; Mirkovic, Mihailo; Mihailovic-Vucinic, Violeta; Aleksic, Vuk; Covickovic-Sternic, Nadezda (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2014)
BACKGROUND: Involvement of the central nervous system is registered in a relatively small number of patients with sarcoidosis. In this article we present two cases with various neurological symptoms that fulfill criteria for neurosarcoidosis (NS). In addition, we review the literature on NS with special attention to isolated cranial nerve involvement. METHODS AND RESULTS: First patient: Neurological examination identified multiple cranial neuropathy, moderate right-sided hemiparesis, polyradiculoneuritis of the lower limbs and positive meningeal signs. Laboratory tests showed serum and cerebrospinal fluid (CSF) inflammatory abnormalities, with increased values of the angiotensin-converting enzyme (ACE). CSF analysis also showed presence of 9 oligoclonal IgG bands. Brain and spine magnetic resonance imaging (MRI) revealed diffuse meningopathy, and focal granulomatous lesion in the body of the L5 vertebra. Lung sarcoidosis was confirmed by additional diagnostic procedures. The patient was treated with Methylprednisolone and a tapering course of oral Prednisone, which reduced the pain in the back and legs and improved the strength of the right leg. However, the other neurological deficiencies remained. After confirming lung sarcoidosis, the patient received Methotrexate in addition to Prednisone but during the following 2 years the patient's condition progressively worsened and ended in death. Second patient: Neurological findings showed weakness of the right n. oculomotorius and the right n. trochlearis, as well as the right-side face weakness. We found raised level of the ACE in serum and CSF. Thorax high-definition computed tomography (HDCTT) showed ribbon-like domains of discrete changes in the pulmonary parenchyma. MRI of the brain showed multiple white matter lesions. This patient also received Methylprednisolone followed by Prednisone, and after two months, ocular motility normalized. CONCLUSION: The diagnosis of NS is always a challenge. For this rerason definitive diagnosis requires the exclusion of other causes of neuropathy. Multiple cranial neuropathies should always arouse suspicion of NS.
Keywords: Magnetic Resonance Imaging; Female; Central Nervous System Diseases; ženské pohlaví; Tomography, X-Ray Computed; lidé; Sarcoidosis; magnetická rezonanční tomografie; mozek; Cranial Nerve Diseases; Male; sarkoidóza; Aged; Brain; nemoci centrálního nervového systému; nemoci kraniálních nervů; počítačová rentgenová tomografie; lidé středního věku; senioři; mužské pohlaví; Middle Aged; Humans